Condensed Matter: Electronic Structure, Electrical, Magnetic, and Optical Properties : Electronic Structure Reconstruction across the Antiferromagnetic Transition in TaFe1.23Te3 Spin Ladder. (4th February 2015) - Xu, Min; Wang, Li-Min; Peng, Rui; Ge, Qing-Qin; Chen, Fei; Ye, Zi-Rong; Zhang, Yan; Chen, Su-Di; Xia, Miao; Liu, Rong-Hua; Shi, Ming; Chen, Xian-Hui; et al.
Abstract: Employing the angle-resolved photoemission spectroscopy we study the electronic structure of TaFe1.23 Te3, a two-leg spin ladder compound with a novel antiferromagnetic ground state. Quasi-two-dimensional (2D) Fermi surface is observed, with sizable inter-ladder hopping. Moreover, instead of observing an energy gap at the Fermi surface in the antiferromagnetic state, we observe the shifts of various bands. Combining these observations with density-functional-theory calculations, we propose that the large scale reconstruction of the electronic structure, caused by the interactions between the coexisting itinerant electrons and local moments, is most likely the driving force of the magnetic transition. Thus TaFe1.23 Te3 serves as a simpler platform that contains similar ingredients to the parent compounds of iron-based superconductors.